REPURPOSING A BUSINESS LEARNING OUTCOMES ASSESSMENT TO COLLEGE STUDENTS OUTSIDE OF THE UNITED STATES: VALIDITY AND RELIABILITY EVIDENCE. Issue 2 (8th August 2014) - Ling, Guangming
ABSTRACT: One concern when repurposing a test to a new population is whether the test is measuring the same construct in a valid and reliable way that is comparable to the intended population. Following the guidelines of the International Test Commission and the ETS Standards for Quality and Fairness, this study was designed to collect evidence in support of repurposing the Major Field Test for the Bachelor's Degree in Business (MFT‐B) for use in undergraduate level business programs outside of the United States. The author examined the test's reliability and internal structure based on 930 senior college students from 9 business programs in Asia, Europe, the Middle East, and South America. Each participating institution satisfied 2 requirements for this study: (a) having a bachelor's level business curriculum that is similar to their U.S. peer programs and (b) using English as the instructional language. The analyses of the data showed that the MFT‐B has the same factor structure for the non‐U.S.–based sample as that for their U.S. peers. In addition, the test scores for the non‐U.S.–based sample are highly reliable (.90) overall, with some variations among the 9 programs. Both types of evidence support the notion that the MFT‐B is appropriate when repurposed for use with non‐U.S.–based business programs.